Chloroquine induces human mononuclear phagocytes to inhibit and kill Cryptococcus neoformans by a mechanism independent of iron deprivation. - Levitz, S M (1997)
Infections due to Cryptococcus neoformans are common in AIDS patients. We investigated the effect of chloroquine, which raises the pH of phagolysosomes, on the anticryptococcal activity of mononuclear phagocytes. C. neoformans multiplied within monocyte-derived macrophages (MDM) in the absence of chloroquine but were killed with the addition of chloroquine. Ammonium chloride was also beneficial, suggesting that effects were mediated by alkalinizing the phagolysosome. Chloroquine inhibits growth of other intracellular pathogens by limiting iron availability. However, chloroquine-induced augmentation of MDM anticryptococcal activity was unaffected by iron nitriloacetate, demonstrating that chloroquine worked by a mechanism independent of iron deprivation. There was an inverse correlation between growth of C. neoformans in cell-free media and pH, suggesting that some of the effect of chloroquine on the anticryptococcal activity of MDM could be explained by relatively poor growth at higher pH. Chloroquine enhanced MDM anticryptococcal activity against all tested cryptococcal strains except for one large-capsule strain which was not phagocytosed. Positive effects of chloroquine were also seen in monocytes from both HIV-infected and -uninfected donors. Finally, chloroquine was therapeutic in experimental cryptococcosis in outbred and severe combined immunodeficient mice. Thus, chloroquine enhances the activity of mononuclear phagocytes against C. neoformans by iron-independent, pH-dependent mechanisms and is therapeutic in murine models of cryptococcosis. Chloroquine might have clinical utility for the prophylaxis and treatment of human cryptococcosis.